Biochemical fingerprint of colorectal cancer cell lines using label‐free live single‐cell Raman spectroscopy. (2nd May 2018) - Gala de Pablo, Julia; Armistead, Fern J.; Peyman, Sally A.; Bonthron, David; Lones, Michael; Smith, Stephen; Evans, Stephen D.
Abstract: Label‐free live single‐cell Raman spectroscopy was used to obtain a chemical fingerprint of colorectal cancer cells including the classification of the SW480 and SW620 cell line model system, derived from primary and secondary tumour cells from the same patient. High‐quality Raman spectra were acquired from hundreds of live cells, showing high reproducibility between experiments. Principal component analysis with linear discriminant analysis yielded the best cell classification, with an accuracy of 98.7 ± 0.3% (standard error) when compared with discrimination trees or support vector machines. SW480 showed higher content of the disordered secondary protein structure Amide III band, whereas SW620 showed larger α‐helix and β‐sheet band content. The SW620 cell line also displayed higher nucleic acid, phosphates, saccharide, and CH2 content. HL60, HT29, HCT116, SW620, and SW480 live single‐cell spectra were classified using principal component analysis or linear discriminant analysis with an accuracy of 92.4 ± 0.4% (standard error), showing differences mainly in the β‐sheet content, the cytochrome C bands, the CH‐stretching regions, the lactate contributions, and the DNA content. The lipids contributions above 2, 900 cm −1 and the lactate contributions at 1, 785 cm −1 appeared to be dependent on the colorectal adenocarcinoma stage, the advanced stage cell lines showing lower lipid, and higher lactate content. The results demonstrate that these cell lines can be distinguished with high confidence, suggesting that Raman spectroscopy on live cells can distinguish between different disease stages, and could play an important role clinically as a diagnostic tool for cell phenotyping. Abstract : Single‐cell spectra of hundreds of live colorectal cancer cells were obtained, including the SW480 and SW620 adenocarcinoma model system, derived from primary and secondary tumours from the same patient. When normalizing to the Amide I, SW620 showed higher α‐helix and β‐sheet Amide III band, nucleic acids, phosphates, saccharide, and CH2 . HL60, HT29, HCT116, SW620, and SW480 spectra were classified with accuracy of 92.4. Contributions above 2, 900 cm −1 decreased and lactate contributions at 1, 785 cm −1 increased with advancing adenocarcinoma stage.